Requirement of Npc1 and availability of cholesterol for early embryonic cell movements in zebrafish[S] - Tyler Schwend (Journal of Lipid Research, 2011)
Abstract Niemann-Pick disease, type C (NP-C), often associated with Niemann-Pick disease, type C1 (NPC1) mutations, is a cholesterol-storage disorder characterized by cellular lipid accumulation, neurodegeneration, and reduced steroid production. To study NPC1 function in vivo, we cloned zebrafish npc1 and analyzed its gene expression and activity by reducing Npc1 protein with morpholino (MO)-oligonucleotides. Filipin staining in npc1-morphant cells was punctate, suggesting abnormal accumulation of cholesterol. Developmentally, reducing Npc1 did not disrupt early cell fate or survival; however, early morphogenetic movements were delayed, and the actin cytoskeleton network was abnormal. MO-induced defects were rescued with ectopic expression of mouse NPC1, demonstrating functional gene conservation, and by treatments with steroids pregnenolone or dexamethasone, suggesting that reduced steroidogenesis contributed to abnormal cell movements. Cell death was found in anterior tissues of npc1 morphants at later stages, consistent with findings in mammals. Collectively, these studies show that npc1 is required early for proper cell movement and cholesterol localization and later for cell survival.